Major and Trace-Element Chemistry of Cr-Spinel in Upper Mantle Xenoliths from East Antarctica - Alexandre Andronikov; Irina Andronikova; Ondrej Pour (Minerals, 2022)
Cr-spinels in the upper mantle peridotite xenoliths from two Late Mesozoic intrusions of alkaline-ultramafic rocks in Jetty Peninsula (East Antarctica) were studied in situ for their major and trace-element compositions by SEM and LA-ICP-MS. The upper mantle xenoliths were collected from the magmatic bodies “sampled” from different upper mantle domains. One domain was represented by mostly lherzolites (Cpx-poor Spl, Cpx-rich Spl and Spl-Grt) and another one by Spl harzburgites and dunites. Spinels occur as grains of different shapes, sizes and origins. Three main textural types of spinel were identified: primary spinel represented by clean homogeneous grains, a rim of recrystallization/resorption surrounding primary spinel grains and irregular interstitial resorbed grains. Primary spinels are characterized by the concentrations of Al2O3 21–51 wt%, MgO 15–20 wt%, FeO 10–24 wt% and Cr2O3 14–37 wt% with the Cr# of 0.16–0.54. Most trace elements are present in spinels in very low amounts. Only Ti, V, Mn, Co, Ni, Zn and Ga display concentrations in the range of tens to hundreds (up to thousands) ppm. Concentrations of other trace elements vary from below the detection limit to <10 ppm. Spinel major oxide and trace element features allowed the suggestion that the studied upper mantle peridotites represent both simple melt residues and residues strongly influenced by the MORB-like and the SSZ-related melts. The MORB-like melts may be related to the beginning of the Lambert–Amery rift system development, whereas SSZ-like melts could be related to reactivation of SSZ material buried during much earlier amalgamation of East Antarctica.